The role of lead-up drills in tumbling - Elliott, B.; McLean, T.; Alderson, J. (ISBS - Conference Proceedings Archive (Konstanz), 2005)
An analysis of three commonly used lead-up drills in tumbling was undertaken to assess the validity in replicating key mechanical variables of a foundation tumble row. Six gymnasts (3 intermediate and 3 elite) were analyzed using a 12-camera Vicon analysis system operating at 250 Hz. Data were then modeled and filtered through Vicon Workstation and processed through Matlab (Version 7.0). Similarities were assumed if the difference in performance was less than one standard deviation away from the mean for variables from the tumble row. Results indicate that the corbette and set jump drills were more likely to produce mechanical variables in preparation for the "tumble row" than the round-off drill. Elite gymnasts in general displayed mechanical characteristics more related to superior performance than the intermediate gymnasts both in the drills and the "tumble row".